2002
DOI: 10.1016/s0364-0213(02)00087-3
|View full text |Cite
|
Sign up to set email alerts
|

Gesture offers insight into problem-solving in adults and children

Abstract: When asked to explain their solutions to a problem, both adults and children gesture as they talk. These gestures at times convey information that is not conveyed in speech and thus reveal thoughts that are distinct from those revealed in speech. In this study, we use the classic Tower of Hanoi puzzle to validate the claim that gesture and speech taken together can reflect the activation of two cognitive strategies within a single response. The Tower of Hanoi is a well-studied puzzle, known to be most efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…The effects of explaining with gestures on subsequent performance (Switch and No-Switch conditions) are directly compared to a no-explanation control condition. A no-explanation condition rather than an explaining-without-gestures condition was chosen, as it has been shown that people routinely gesture when talking about solving the TOH task (Garber & Goldin-Meadow, 2002). Furthermore, in accordance with the pilot study conducted by Beilock and Goldin-Meadow (2010), we have observed that participants told not to gesture generally experience difficulties fully explaining their moves.…”
Section: Present Experimentsmentioning
confidence: 90%
“…The effects of explaining with gestures on subsequent performance (Switch and No-Switch conditions) are directly compared to a no-explanation control condition. A no-explanation condition rather than an explaining-without-gestures condition was chosen, as it has been shown that people routinely gesture when talking about solving the TOH task (Garber & Goldin-Meadow, 2002). Furthermore, in accordance with the pilot study conducted by Beilock and Goldin-Meadow (2010), we have observed that participants told not to gesture generally experience difficulties fully explaining their moves.…”
Section: Present Experimentsmentioning
confidence: 90%
“…Under this alternative view, the mental representation containing weight was reflected in gesture, rather than caused by gesture. Previous work has found that participants (adults and children) asked to explain TOH with the disks present do gesture throughout their explanations (Garber & Goldin-Meadow, 2002). If we are correct that gesture leads to (as opposed to reflects) the construction of a mental representation containing weight, the gestures that adults produce in the presence of the TOH disks ought to have the same detrimental effect on TOH2 performance with switched disks as the gestures produced in the absence of the disks.…”
Section: Discussionmentioning
confidence: 99%
“…There is ample evidence that the production of these gestures reflects thought (Alibali, Bassok, Solomon, Syc & Goldin-Meadow, 1999; Garber & Goldin-Meadow, 2002; Cook & Tanenhaus, 2009), predicts changes in thought (Church & Goldin-Meadow, 1986; Alibali & Goldin-Meadow, 1993; Perry, Church & Goldin-Meadow, 1988; Ping, Decatur, Larson, Zinchenko & Goldin-Meadow, under review), and even elicits changes in thought (Broaders, Cook, Mitchell & Goldin-Meadow, 2007; Singer & Goldin-Meadow 2005; Goldin-Meadow, Cook & Mitchell 2009; Goldin-Meadow, Levine, Zinchenko, Yip, Hemani, & Factor, 2012). …”
mentioning
confidence: 99%
“…Speakers of all ages produce utterances in which gesture conveys information that is different from the information conveyed in speech (e.g. Stone, Webb & Mahootian, 1991 ;Alibali, Bassok, Olseth, Syc & Goldin-Meadow, 1999 ;Beattie & Shovelton, 1999 ;Garber & Goldin-Meadow, 2002). And even adults will produce many gesture+speech mismatches when they have not yet mastered a task and are in a state of transition (Perry & Elder, 1997).…”
Section: The Function Of Supplementary Gesture+speech Combinations Fomentioning
confidence: 99%